Normal perception of Mooney faces in developmental prosopagnosia: Evidence from the N170 component and rapid neural adaptation. Issue 1 (19th September 2014) - Towler, John; Gosling, Angela; Duchaine, Bradley; Eimer, Martin
Abstract : Individuals with developmental prosopagnosia (DP) have a severe difficulty recognizing the faces of known individuals in the absence of any history of neurological damage. These recognition problems may be linked to selective deficits in the holistic/configural processing of faces. We used two‐tone Mooney images to study the processing of faces versus non‐face objects in DP when it is based on holistic information (or the facial gestalt) in the absence of obvious local cues about facial features. A rapid adaptation procedure was employed for a group of 16 DPs. Naturalistic photographs of upright faces were preceded by upright or inverted Mooney faces or by Mooney houses. DPs showed face‐sensitive N170 components in response to Mooney faces versus houses, and N170 amplitude reductions for inverted as compared to upright Mooney faces. They also showed the typical pattern of N170 adaptation effects, with reduced N170 components when upright naturalistic test faces were preceded by upright Mooney faces, demonstrating that the perception of Mooney and naturalistic faces recruits shared neural populations. Our findings demonstrate that individuals with DP can utilize global information about face configurations for categorical discriminations between faces and non‐face objects, and suggest that face processing deficits emerge primarily at more fine‐grained higher level stages of face perception.